The Role of Law and Human Rights in Ensuring Social Justice and Poverty Eradication Through Social Assistance - Ningsih, Putu Ayu Veguita Putri; Wahyudi, Slamet Tri (Rechtsvinding, 2025)
Poverty is a scourge in this country. In this case, the government uses a social assistance approach in the form of basic food supplies for the poor. This raises questions when confronted with the concept of the rule of law and human rights in relation to the state's solution in providing social assistance to them. The research method used is normative juridical with a legislative approach and a conceptual approach. The results of the study show that the state uses a social assistance approach in the form of basic food supplies as a short-term solution, ignoring the actual economic conditions. Then, the state needs to formulate concrete legislation in order to provide definite social assistance to the lower-middle class so that the presence of the state as a state based on the rule of law and human rights becomes more certain by providing long-term solutions.